The Work of Artists. - Rocco, Linda (Art Monthly, 2023)
The article argues for collaborative ways of working and alternative models of cultural and economic exchange among artists to combat the marketization of art and culture in neoliberal societies. Topics discussed include systemic injustice ingrained in museum practices, hierarchy in contemporary art, implementation of digital technologies in the creative industry sector and formal art education, and Decentralised Autonomous Organisations (DAO) as an alternative to centralised topdown structure.